KEANEKARAGAMAN RAYAP PADA LAHAN TEGAKAN JATI DI KABUPATEN TULUNGAGUNG DAN WONOGIRI - Adhi Gilang Indrawan; Nadzirum Mubin; Arinana (BPFP Universitas Bengkulu, 2025)
[TERMITE DIVERSITY IN TEAK IN TULUNGAGUNG AND WONOGIRI REGENCIES]. Termites are insects that have a very high potential for damage to various stands such as teak. This study aimed to identify the diversity of termite species in teak stands in Tulungagung and Wonogiri regencies. Sampling using the transect method with a transect area of 10 m x 60 m and feeding with pine wood placed in five sub-districts in Tulungagung Regency (Kalidawir, Pucanglaban, Tanggunggunung, Campur Darat, and Ngunut) and five sub-districts in Wonogiri (Jatiroto, Jatisrono, Sidoharjo, Slogohimo, and Purwantoro). The results showed that at least four termite species were found, Macrotermes gilvus, Odontotermes sp., Microtermes insperatus, and Nasutitermes havilandi. Termite diversity in Wonogiri was classified as medium with the highest H’ value (1.08), while termite diversity in Tulungagung was low with the lowest H’ (0.59). The dominance value of termite species in both districts was classified as medium and the evenness value in all observation locations showed an average high evenness index value. The results of the non-metric multidimensional scalling analysis showed that Jatiroto Subdistrict and Ngunut Subdistrict have a high level of species similarity (0.90).